Entrepreneurial Resilience Strategies in Economic Crises: A Case Study of SMEs in Indonesia - Arifin, Zainal (Eastasouth Institute, 2025)
Small and Medium Enterprises (SMEs) are highly vulnerable to economic crises, particularly in developing economies such as Indonesia, where limited resources and institutional constraints intensify business uncertainty. This study explores how Indonesian SME owners build and enact entrepreneurial resilience during periods of economic crisis. Employing a qualitative case study approach, data were collected through in-depth interviews with five SME owners from different business sectors. Thematic analysis reveals that entrepreneurial resilience is a multidimensional and dynamic process shaped by entrepreneurs’ perceptions of crisis, strategic adaptation, innovation, digital transformation, social capital, and personal perseverance. The findings show that resilience is not merely an individual psychological trait, but an ongoing practice embedded in daily business decisions, informal networks, and experiential learning. Family support, trust-based relationships with suppliers and customers, and incremental innovation emerged as critical enablers of business survival. This study contributes to the entrepreneurial resilience literature by providing contextual insights from a developing-country perspective and highlights the importance of integrating strategic, social, and behavioral dimensions in understanding SME resilience. Practical implications are offered for policymakers and support institutions aiming to strengthen SME sustainability during economic disruptions.